2006
DOI: 10.1007/s11325-005-0042-x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal pressure recordings to detect obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is a common disease. Given the costs of in-laboratory polysomnography (PSG), alternative ambulatory methods for accurate diagnosis are desirable. The objective of this study was to evaluate the performance of a simple device (SleepCheck) to identify patients with sleep apnea. A total of 30 consecutive patients with suspected OSA syndrome referred to the sleep clinic were prospectively evaluated with standard PSG and SleepCheck simultaneously during an in-laboratory, supervised ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
2
42
0
2
Order By: Relevance
“…The other is that subjects with relatively low AHI (AHI ,20) are less affected by the bias, resulting in less adverse effects for the diagnostic ability. Other reports [11,13,25,26] on validation of automated analysis do not show such an AHI-dependent systematic bias but rather a random and larger bias.…”
Section: Performance Of the Algorithmmentioning
confidence: 81%
See 1 more Smart Citation
“…The other is that subjects with relatively low AHI (AHI ,20) are less affected by the bias, resulting in less adverse effects for the diagnostic ability. Other reports [11,13,25,26] on validation of automated analysis do not show such an AHI-dependent systematic bias but rather a random and larger bias.…”
Section: Performance Of the Algorithmmentioning
confidence: 81%
“…Recently, AYAPPA et al [10] reported that manual analysis of the flow signal could provide a result similar to that obtained by full PSG analysis. Furthermore, several single-channel airflow monitors have been developed for automated detection of SDB [11][12][13]. Studies for the accuracy of these monitors have provided conflicting results and it is unclear whether performance depends on the signal acquisition system, including the sensor, or on the analytical algorithm.…”
mentioning
confidence: 99%
“…ApneaLink was shown to be useful in screening high-risk patients [66,67]. Nasal pressure recordings in 30 subjects using SleepCheck, an ambulatory device, overscored disordered breathing events in subjects with OSA, but correlation was reported with the apnoea-hypopnoea index and respiratory disturbance index [68]. The Embletta is a portable device that has been shown to produce AHI results that are correlated with AHI results from sleep laboratory polysomnography [69].…”
Section: Portable Screening Devicesmentioning
confidence: 99%
“…Three different single NFlow devices (SleepCheck, Flow Wizard, RU-sleeping) and one NFlow-oximetry combined device (ApneaLink) have been tested against PSG, all with high agreement for OSAS. 18,39,42,43 In two studies, oximetry and NFlow recording did have equivalent accuracy for diagnosing OSAS in the home setting. 43,44 Chai-Coetzer et al 39 reported less data loss (3%) (with oximetry) compared to NFlow (9%).…”
mentioning
confidence: 93%